The Determinants of Stock Market Performance Among Registered Companies in Tanzania: A Case of Dar Es Salaam Stock Exchange - Victor Mvanda; Pastory Dickson; Albinus Majula (International Journal of Management, Accounting and Economics)
The purpose of this study is to ascertain how sales growth affects the stock market performance of businesses listed on the Dar es Salaam Stock Exchange (DSE). More specifically, the study determined the correlation between sales growth and stock market performance. A quantitative method was used to analyze the secondary data from 14 companies out of 28 registered with the DSE. Furthermore, the analysis of quantitative data using the Generalized Linear Equation Model (GLM), Mixed Generalized Linear Regression Model (MGLM), and Panel Regression Model (PRM) helped to obtain results for generalization. Findings indicated that sales growth had a statistically significant negative impact on the firm’s performance by 0.01 according to the pooled GLM in Tanzania. The fixed and random effect model revealed a non-statistically significant effect despite the unbalanced panel effects; as a result, sales growth had a 0.516 negative influence on firm performance. As a result, the financial performance of the organization and sales growth were inversely related. The study recommended that companies registered with the DSE should well leverage so as to benefit from the performance competitiveness of the DSE public market.